SMART SHOPPER ERA: EXPLORING THE ROLE OF CONTENT AND CUSTOMER REVIEWS ON THE PURCHASE OF WARDAH COSMETIC PRODUCTS ON SHOPEE E-COMMERCE PLATFORM - Prabowo, Ari; Sari, Tika Nirmala; Parhusip, Austin Alexander (Penelitian dan Pengembangan Ilmu, 2025)
The research objective is to determine and analyze the partial and simultaneous influence of content marketing, online customer reviews, and e-wom on purchasing decisions. This type of research approach is causal associative research, to determine the relationship between one or more variables, with the research method used is quantitative method. The population in this study are all consumers who shop on the shopee platform, the number of which cannot be known with certainty, so due to limited time, costs and others, the research sample was taken using the Zikmund Formula method by determining 100 respondents, namely consumers who shop on the shopee platform. The results of the study explain that content marketing, online customer reviews, and e-wom partially and simultaneously have a significant effect on purchasing decisions. The determination test results explain that the Adjusted R Square of 0.782 means 78.2% of the factors that influence purchasing decisions. While the remaining 21.8% can be explained by other factors not examined in this study.